Post-Notification Arrangements in Merging Business Entities (Mergers) as an Effort to Prevent Unfair Business Competition - Fahamsyah, Ermanto; Suri, Fadillah Atika (Lentera Hukum, 2019)
One way a business actor strengthens their business is through cooperation with other business actors. One form of cooperation is a "merger" or another term, "merging." Mergers carried out by business actors can result in monopolistic practices or unfair business competition. A merger of competition aspects is regulated in Article 28 and 29 of Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition which provides regulation regarding post-notification of mergers. Commission Regulation No. 1 of 2009 on Pre-Notification of Mergers, Consolidations, and Acquisitions gives a different arrangement, namely in the form of pre-notification to business actors. This difference in notification arrangements provides ineffectiveness and inefficiency for business actors. Keywords: Post-Notification, Mergers, Unfair Business Competition.